(3eSGFd hQOJ ef GdTQja fhQ GdOjf GdMSf Hf jMjis - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ HGdYde bdhH GdYGQajf , hCScf GdfahS Edi HQO Gdjbjf s
(3BNQgG (B:s
(3agPG eG EJab ai gPg GdeSGFd Ydi bOQ GdEecGf , hJQGOa GdGTZGd , hVjb GdeLGd hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B11s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis